2010
DOI: 10.1080/1573062x.2010.484501
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of municipal drinking water distribution system energy use to system properties

Abstract: Municipal Drinking Water Distribution Systems (MDWDSs) consume a significant quantity of energy to transport water, thereby exacerbating greenhouse gas emissions and global climate change. The current study is a sensitivity analysis that uses a network solver to quantify energy savings due to the alteration of three system propertiessystem-wide water demand, storage tank parameters (maximum water level, diameter, elevation), and pumping stations (horsepower, number of boosters, and their locations) of seven di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…One of the key hypotheses in their distribution system sensitivity analysis was that operational energy consumption is reduced with lower demand because of the reduced pipe velocity and friction energy losses. However, the relationship between demand flow and energy use was not linear in the largest water distribution network examined by Ghimire and Barkdoll (2010). However, the relationship between demand flow and energy use was not linear in the largest water distribution network examined by Ghimire and Barkdoll (2010).…”
Section: © American Water Work Associationmentioning
confidence: 91%
See 2 more Smart Citations
“…One of the key hypotheses in their distribution system sensitivity analysis was that operational energy consumption is reduced with lower demand because of the reduced pipe velocity and friction energy losses. However, the relationship between demand flow and energy use was not linear in the largest water distribution network examined by Ghimire and Barkdoll (2010). However, the relationship between demand flow and energy use was not linear in the largest water distribution network examined by Ghimire and Barkdoll (2010).…”
Section: © American Water Work Associationmentioning
confidence: 91%
“…Ghimire and Barkdoll (2010) commented on the relationship between water demand and system energy consumption. Ghimire and Barkdoll (2010) verified both this assumption and work previously completed by Walski (1993) that showed that energy cost is a fairly linear function of system flow, particularly for smaller systems. Ghimire and Barkdoll (2010) verified both this assumption and work previously completed by Walski (1993) that showed that energy cost is a fairly linear function of system flow, particularly for smaller systems.…”
Section: © American Water Work Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pump scheduling can reduce WDS pumping energy cost. Ghimire and Barkdoll (2010) carried out a sensitivity analysis by quantifying energy savings due to the alteration of system-wide water demand, storage tank parameters and pumping stations. In essence, energy requirement in water supply systems can be a useful way of comparing designs and operation.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Ghimire and Barkdoll (2010) found that reduction in water demand, main pump horsepower, and booster horsepower can lead to significant energy savings from operations of WDSs.…”
Section: N O T C O P Y E D I T E Dmentioning
confidence: 99%